The Development of Science-Biology Learning Instrument Oriented to Mangrove Forest for Junior High School Students - Zaini, Muhammad; Asnida, Dini Juli (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This research aims to develop a science-biology learning instrument that is practical and effective. The stage of development using procedural model consisting of: a) the identification of problem, b) describes the objectives, and c) establishes the development model. The stage of products testing included: a) test, b) to evaluate, and c) communicate the results. The subjects were students of SMPN 3 and 5, Loban River, Tanah Bumbu regency. Individual testing was done in SMPN3. Small group and field test was conducted in SMPN 5. The data of practicality of learning instruments includes: a) the usage of lesson plan (RPP), and b) the response of students to learning process. The data of effectiveness of learning instruments includes: a) the cognitive learning outcomes, b) the assessment results of critical thinking skills, c) the assessment results of behavioral characteristics, d) the assessment results of social skills, and e) the effectiveness of students in learning process. Data were collected through tests and observation and analyzed descriptively. The results of research in the development stage, including: a) problem identification such as topic selection of learning and the determination of learning environment, b) learning objectives based on the ABCD rule and learning outcomes, such as critical thinking skills, c) development model. The research results in the testing product stage demonstrated the practicality of the learning instrument has been reached. It is based on: a) the usage of RPP which were already good, and b) most students have responded positively to the learning process. The effectiveness of learning intrument has also been fulfilled. It is based on: a) cognitive learning outcomes that have been completed, b) the assessment results of critical thinking skills, behavioral characteristics, and social skills, that have achieved good category, e) the student's liveliness in learning process which were already visible.Keywords:Â Effectiveness, learning instruments, mangrove forests, practicality, science-biology